Field-aligned electron-cyclotron waves in a straight mirror-trapped plasma with anisotropic temperature - Grishanov, N.I; Azarenkov, N.A. (Вопросы атомной науки и техники, 2014)
Dispersion characteristics have been analyzed for field-aligned electron-cyclotron waves (named also as the right-hand polarized or extraordinary waves) in a two-dimensional cylindrical magnetic mirror-trapped plasma including the electrons with anisotropic temperature (pressure). It is shown that the instability of these waves is possible only in the range below the minimal electron-cyclotron frequency, that much smaller than the gyrotron frequency used for ECR power input into the plasma, under the condition when the perpendicular temperature of resonant electrons is larger than their parallel temperature. Проанализированы дисперсионные характеристики электронно-циклотронных (правополяризованных, необыкновенных) волн в двумерно-неоднородном аксиально-симметричном пробкотроне, содержащем электроны с анизотропной температурой (давлением). Показано, что неустойчивость этих волн возможна лишь в области частот ниже минимальной электронно-циклотронной частоты, то есть при частотах, много меньших гиротронной частоты электромагнитных волн, используемых для ЭЦР-нагрева плазмы, при условии, что поперечная температура резонансных электронов больше их продольной температуры. Проаналізовано дисперсійні характеристики електронно-циклотронних (правополярізованих, незвичайних) хвиль у двовимірно-неоднорідному аксіально-симетричному пробкотроні, що містить електрони з анізотропною температурою (тиском). Доведено, що нестійкість цих хвиль є можливою лише в діапазоні частот нижче мінімальної електронно-циклотронної частоти, тобто при частотах, багато менших гіротронної частоти електромагнітних хвиль, що використовуються для ЕЦР-нагрівання плазми, за умови, що поперечна температура резонансних електронів є більшою за їхню поздовжню температуру.